2013
DOI: 10.20343/teachlearninqu.1.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Going Public with Pedagogical Inquiries: SoTL as a Methodology for Faculty Professional Development

Abstract: In this paper, I discuss SoTL as a methodology for the professional development of academics. I propose that as an agentic form of inquiry that focuses on processes, boundary-crossing, and making pub lic its findings, SoTL is a sophisticated methodology that brings the activities of teaching and research in close alignment, and contributes to developing an approach to inquiry that differs from what I have called "managed" research. I propose that, as a methodology for professional development, SoTL provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Nevertheless, it is also notable that participants continued to reiterate many of the benefits of the SI nearly one year after its completion. Unlike academics who abandon ideas learned in educational development initiatives upon returning to their day-to-day work (Fanghanel, 2013), some participants reported implementing partnership projects developed at the SI, initiating new ones, and inviting new people in their home contexts into the process (including some participants at the 2017 institute, who noted they had been engaged in partnership initiatives by colleagues returning from the 2016 event). While the specifics of participants' contexts impinged on whether and how they followed up, they generally reported that the SI was an energising experience that generated ideas for moving forward-even when institutional climates might feel inhospitable and change might be slow and uneven.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is also notable that participants continued to reiterate many of the benefits of the SI nearly one year after its completion. Unlike academics who abandon ideas learned in educational development initiatives upon returning to their day-to-day work (Fanghanel, 2013), some participants reported implementing partnership projects developed at the SI, initiating new ones, and inviting new people in their home contexts into the process (including some participants at the 2017 institute, who noted they had been engaged in partnership initiatives by colleagues returning from the 2016 event). While the specifics of participants' contexts impinged on whether and how they followed up, they generally reported that the SI was an energising experience that generated ideas for moving forward-even when institutional climates might feel inhospitable and change might be slow and uneven.…”
Section: Discussionmentioning
confidence: 99%
“…Support-and maybe, more importantly, visible support-for SoTL within a department could lead to more sharing and discussion of practice, more opportunities for communities of practice to form, and the benefits of SoTL being seen on a wider scale. Fanghanel (2013) proposes that the approach of SoTL-a focus on processes, boundary (discipline) crossing, and making findings public-makes a useful and sophisticated methodology for professional development.…”
Section: Professional Developmentmentioning
confidence: 99%
“…While we have used a reflective framework (Rolfe et al, 2001) as our methodology for writing this article, and our framing of assessment measures is in keeping with underlying principles of utilization-focused evaluation, we would like to identify or develop an overarching methodology for the approach. Inasmuch as our approach reflects the principles of SoTL, SoTL has also functioned as a tool for professional development, as we have taken a collaborative approach to enhancing our practice (Fanghanel, 2013).…”
Section: Now What?mentioning
confidence: 99%